İzole Karın Travmalarının Demografik ve Klinik Özelliklerinin Değerlendirilmesi - Acar, Ethem (Ondokuz Mayıs Üniversitesi, Tıp Fakultesi, 2010)
İzole karın travması nedeniyle acil servise başvuran 16 yaş ve üzerindeki erişkin olguların; demografik özelliklerini, karın travmalarının klinik ve laboratuar bulgularını, tedavilerini, mortalite oranlarını incelemeyi ve bu konuda ülkemizdeki literatüre katkıda bulunmayı amaçladık.

We aimed to investigate demographical features, clinical and laboratory findings, treatment, rates of mortality of patients admitted to emergency department with isolated abdominal trauma older than 16 years and contribute to the literature.
Evaluation of Demographical and Clinical Characteristics of Isolated Abdominal Traumas
Tez (tıpta uzmanlık) -- Ondokuz Mayıs Üniversitesi, 2010
Libra Kayıt No: 76788
Keywords: İlk ve Acil Yardım; Abdomen; Abdominal Yaralanmalar; Acil Servis-Hastane; Demografi; Retrospektif Çalışmalar; Yaralar ve Yaralanmalar; Emergency and First Aid; Abdomen; Abdominal Injuries; Emergency Service-Hospital; Demography; Retrospective Studies; Wounds and Injuries; TEZ TIP A168i 2010